Mechanism of Sodium Storage in Hard Carbon: An X‐Ray Scattering Analysis. Issue 3 (10th December 2019) - Morikawa, Yusuke; Nishimura, Shin‐ichi; Hashimoto, Ryu‐ichi; Ohnuma, Masato; Yamada, Atsuo
Abstract: Hard carbon is a standard anode material for Na‐ion batteries. However, its low crystallinity and diverse microstructures make obtaining a full understanding of the sodium storage mechanism challenging. Here, the results of a systematic ex situ small and wide angle X‐ray scattering study of a series of nanostructured hard carbons, which reveal clear evidence of sodium storage in the graphene–graphene interlayers and nanopores, are presented. Particularly, an emergence of a broad peak around q ≈ 2.0–2.1 Å −1 in the low voltage region is suggested to be an indicator that sodium is densely confined in the nanopores. Thus, classical X‐ray scattering techniques are demonstrated to be effective in elucidating the overall reaction scheme of Na insertion into hard carbon. Abstract : Hard carbon is a common anode material for sodium‐ion batteries. However, its sodium storage mechanism is still controversial. Here, systematic ex situ X‐ray scattering analysis for a series of nanostructured hard carbons reveals that the sodium atoms are densely stored into the nanopores with an appearance of a characteristic scattering peak in the wide‐angle X‐ray scattering pattern.